2002
DOI: 10.1097/00003246-200204000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Citrate anticoagulation in a piglet model of pediatric continuous renal replacement therapy

Abstract: The available literature and our past experience indicate that a prefilter ionized calcium < or =0.4 mmol/L is required to anticoagulate a CRRT circuit; a prefilter serum citrate concentration of 6 mmol/L is required to achieve this. Our multiple regression analysis can be expressed graphically to allow easy calculation of the required citrate flow rate, given the knowledge of the replacement flow rate and blood flow rate. Our results provide the first guidelines for the use of citrate as a regional anticoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Citrate also inhibits platelet aggregation. Nuthall et al found a linear relationship between iCa and serum citrate levels in an animal model of RCA in continuous venovenous hemofiltration [26]. Bakker et al found a hyperbolic relationship between iCa and measured serum citrate levels in ten adult patients with RCA [27].…”
Section: Discussionmentioning
confidence: 99%
“…Citrate also inhibits platelet aggregation. Nuthall et al found a linear relationship between iCa and serum citrate levels in an animal model of RCA in continuous venovenous hemofiltration [26]. Bakker et al found a hyperbolic relationship between iCa and measured serum citrate levels in ten adult patients with RCA [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our citrate anticoagulation protocol was based on earlier work using an animal model [20], but was similar in all major respects to pediatric protocols published by Bunchman et al [17] and Chadha et al [18]. The PRISMA hemofiltration system with M-60 size filter (COBE, Lakewood, Colo., USA) was used for all patients.…”
Section: Cvvh Protocolmentioning
confidence: 99%
“…The rate was adjusted following a published protocol [20] but, in practice, the citrate flow (in ml/min) was 1.5-2 times the blood flow (in ml/h). For example, to anticoagulate a circuit blood flow of 5 ml/kg per min requires an ACD-A flow of 8-10 ml/kg per hour.…”
Section: Cvvh Protocolmentioning
confidence: 99%
See 2 more Smart Citations